Hydrogen Recovery and Fic Increase in The Chemical Industry - Xasanov Diyorjon Ramish o’g’li; Otakuziyeva Vazirahon Usmonjonovna (Web of Journals Publishing, 2023)
The article examines the production of hydrogen in cheap and convenient ways and the improvement of useful processes through these methods.
Keywords: electrolysis, fik, fuel, renewable energy.